58. FACTORS ASSOCIATED WITH THE OUTCOMES OF BENIGN PROSTATIC HYPERPLASIA USING BIPOLAR TRANSURETHRAL ENUCLEATION AT 108 MILITARY CENTRAL HOSPITAL (Vietnam Journal of Community Medicine, 2025)
Objective: To identify factors associated with the outcomes of benign prostatic hyperplasia using bipolar transurethral enucleation at 108 Military Central Hospital from 2024 to 2025.Methods: A prospective, longitudinal descriptive study was conducted on a case series of 68 patients with benign prostatic hyperplasia who underwent bipolar transurethral enucleation.Results: The mean operative time was 54.2±17.5 minutes, with a median of 50 minutes (IQR 40-65). Analysis revealed that factors significantly associated with operative time included preoperative prostate volume (p
Keywords: Benign prostatic hyperplasia; bipolar; transurethral enucleation; associated factors.